Flexible Solar Yarns with 15.7% Power Conversion Efficiency, Based on Electrospun Perovskite Composite Nanofibers. Issue 9 (1st July 2020) - Li, Qian; Balilonda, Andrew; Ali, Aizaz; Jose, Rajan; Zabihi, Fatemeh; Yang, Shengyuan; Ramakrishna, Seeram; Zhu, Meifang
Abstract : A flexible perovskite solar yarn with an impressive active lifetime (>216 h) and an exceptional photon conversion efficiency is prepared under ordinary conditions. The champion device demonstrates an average linear mass density of 0.89 mg cm −1 and can be bent over a loop diameter of 2.5 mm, with a negligible efficiency loss. Photoactive nanofibers composed of a polyvinylpyrrolidone (PVP) central strain and a perovskite phase on the surface (with average grain size of 275 ± 14.3 nm), are prepared by electrospinning, at 18 kV, relative humidity of 75%, and a temperature of 25 °C. This bilayered configuration promises superior mechanical strength and flexibility, together with an excellent photovoltaic character, compared with their dip coated counterparts. Photoactive perovskite nanofibers are incorporated into a plied‐solar yarn, with an organic hole‐conductive layer, poly(3‐hexylthiophene‐2, 5‐diyl)‐coated on silver yarn electrode, and a composite electron conductive layer, phenyl‐C61 ‐butyric acid methyl ester (PC61 BM)‐SnO2 coated on a carbon yarn. An individual double‐twisted solar yarns yields 15.7% champion power conversion efficiency, while a 30.5 mm × 30.5 mm active area of plain‐woven fabric generates a maximum power density of 1.26 mW cm −2 under one sun (1000 W m −2 ) solar illumination. Abstract : Herein, perovskite composite nanofibers are incorporated into a solar yarn through an electrospinning process, to work as the photoactive layer of the device. Electrospinning is conducted at high relative humidity (75%) and voltage (17 kV) to enhance perovskite crystal growth on polyvinylpyrrolidone (PVP) nanofibers. The resulting yarn demonstrates a 15.7% efficiency, with a good absorption peak, flexibility, and increased active lifetime.